C.1 Time Metrics and Clinical Outcomes of Thrombectomy in Acute Stroke Patients Before and After Implementation of COVID-19 Infection Protocols in Nine Canadian Stroke Centres. (November 2021) - Zhu, S; Tsehmaister-Abitbul, V; Stotts, G; Fahed, R; Pettem, H; Aviv, R; Agid, R; Pikula, A; Shankar, J; Milot, G; Peeling, L; Tampieri, D; et al.
Abstract : Background: The coronavirus disease 2019 (COVID-19) pandemic has led an implementation of institutional infection control protocols. This study will determine the effects of these protocols on outcomes of acute ischemic stroke (AIS) patients treated with endovascular therapy (EVT). Methods: Uninterrupted time series analysis of the impact of COVID-19 safety protocols on AIS patients undergoing EVT. We analyze data from prospectively collected quality improvement databases at 9 centers from March 11, 2019 to March 10, 2021. The primary outcome is 90-day modified Rankin Score (mRS). The secondary outcomes are angiographic time metrics. Results: Preliminary analysis of one stroke center included 214 EVT patients (n=144 pre-pandemic). Baseline characteristics were comparable between the two periods. Time metrics "last seen normal to puncture" (305.7 vs 407.2 min; p=0.05) and "hospital arrival to puncture" (80.4 vs 121.2 min; p=0.04) were significantly longer during pandemic compared to pre-pandemic. We found no significant difference in 90-day mRS (2.0 vs 2.2; p=0.506) or successful EVT rate (89.6% vs 90%; p=0.93). Conclusions: Our results indicate an increase in key time metrics of EVT in AIS during the pandemic, likely related to infection control measures. Despite the delays, we found no difference in clinical outcomes between the two periods.